DYNAMIC EQUIVALENCE: TRANSLATION THEORY - Lina Farsia; Sarair Sarair (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Translation is a product of the process called translating. In translating, a translator has to make sure the translation has the equivalent meaning to the source texts. There many theories on how to have a good translation; one of the theories is dynamic equivalence theory. In this paper, the writers would like to discuss deeper about the use of dynamic equivalence theory in translating process where English as a source language and Bahasa Indonesia as the target language. The implementation of dynamic equivalence theory is discussed together with the examples and explanation about why dynamic equivalence is used and why some words are chosen in translation and not the other words. It shows that when word-to-word translation cannot make sense the meaning of the target language dynamic equivalence theory offers flexibility for the translator to translate and to make sense the meaning of the translation.